Net carbon dioxide exchange rate of a vineyard during the growth cycle - Zermeño-González, Alejandro; Bravo-Escalante, Addy Patricia; Campos-Magaña, Santos Gabriel; Ramírez-Rodríguez, Homero; Méndez-González, Jorge (Revista Mexicana de Ciencias Agrícolas, 2021)
In addition to harvesting of grape for fresh consumption, juice making and wine production, vineyards (Vitis vinifera L.) for their status as woody and long-lived plants can have an important participation in the assimilation and retention of atmospheric carbon. The objective of this study was to evaluate the net carbon dioxide exchange rate of the ecosystem (NEE) in a vineyard during its production cycle, and its relationship to atmospheric carbon sequestration. The study was carried out (from April to December 2018) in an 11-year-old Shiraz cultivar vineyard in the Vinícola San Lorenzo, Parras, Coahuila. The rate of carbon dioxide flow between the vineyard canopy and the atmosphere, through the months of growth was measured with the sensors of an eddy covariance system. From April to November the vineyard acts as an atmospheric carbon sink and during May, June and July the highest NEE values were obtained, with an average value of -3.014 g C m-2 s-1. The carbon stored in the wood of the vineyard plants was 3.35 t C ha-1. These results show that vineyards are agricultural systems that can have a significant role in mitigating atmospheric carbon dioxide, which, coupled with their status as woody-long-lived plants and the large established areas of vineyards in Mexico and the world, are very important carbon storage ecosystems.
Keywords: Viits vinifera L.; carbon sequestration; photosynthesis; photosynthetically active radiation